Distribution of Conduction Velocity (DCV) from measured F-Wave Latency for detection of cervical spondylotic radiculopathy and myelopathy (CRM) - Rahman, M Obaidur; Rabbani, K Siddique-e (Bangladesh Journal of Medical Physics, 2015)
In the previous work of our extended group at Dhaka, Distribution of Conduction Velocity (DCV) of motor nerve fibres in a peripheral nerve trunk was established as an approximate mirror image of Distribution of F-Latency (DFL), for which consecutive 30 to 40 F-latencies were used through multiple stimulation of a peripheral nerve trunk. Using patterns of DFL a considerable amount of experience has been built up in the detection of Cervical Spondylotic Radiculopathy and Myelopathy (CRM). In the present work we have obtained DCV directly from the Conduction Velocity (CV) values obtained from each of the F-latencies. Because of the inverse relationship between latency and velocity, a small variation to the mirror image should be present, particularly when discrete bin widths are used to obtain the frequency distribution. Therefore, one challenge was to choose an appropriate bin width while obtaining DCV directly so that the patterns can be related to those of DFL easily for the detection of CRM. To obtain DFL our extended group at Dhaka had used a bin width of 2 ms which gave good results. To choose a corresponding bin width for DCV four recognized measures of central tendency: Average of the range, Median, Mode and Mean (weighted average) were used and the resulting patterns of DCV were compared to that of DFL to determine the percentage of matches with respect to the detection of CRM. It was observed that Median gave the best DCV with 89% matches followed closely by Mode giving 83% match. The other two gave much lower values, 67% and 50%. Therefore, median value gave the best match which could be used to obtain DCV from the CV values directly, for the determination of CRM. Bangladesh Journal of Medical Physics Vol.7 No.1 2014 56-65